2007
DOI: 10.1113/jphysiol.2006.124610
|View full text |Cite
|
Sign up to set email alerts
|

Maternal taurine supplementation in the late pregnant rat stimulates postnatal growth and induces obesity and insulin resistance in adult offspring

Abstract: An adequate supply of taurine during fetal life is important for normal beta-cell development and insulin action. An altered availability of taurine may programme glucose metabolism in utero and result in type 2 diabetes in adult age. We examined whether maternal taurine supplementation in late pregnant rats affects postnatal growth, adult body composition, insulin sensitivity and endogenous insulin secretion in intrauterine growth restricted (IUGR) and normal offspring. Uterine artery ligation or sham operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 42 publications
0
24
1
1
Order By: Relevance
“…Thus, it is unlikely that this learning deficit was related to a general developmental defect indicated by body weight. With respect to pup body weight, these findings were not consisted with studies in rats: 0.5% (Hirano et al, 1984) and 2% (Hultman et al, 2007) taurine supplementation in the mother's drinking water increased pup body weight. For precise analysis of developmental time courses affected taurine supplementation, it will be necessary to increase the number of subjects.…”
Section: Retardation Of Learning By Taurine Supplementationcontrasting
confidence: 72%
“…Thus, it is unlikely that this learning deficit was related to a general developmental defect indicated by body weight. With respect to pup body weight, these findings were not consisted with studies in rats: 0.5% (Hirano et al, 1984) and 2% (Hultman et al, 2007) taurine supplementation in the mother's drinking water increased pup body weight. For precise analysis of developmental time courses affected taurine supplementation, it will be necessary to increase the number of subjects.…”
Section: Retardation Of Learning By Taurine Supplementationcontrasting
confidence: 72%
“…This study did not take maternal BMI into consideration and this may be the reason for these two contradictory findings. In fact, obesity, accompanied by metabolic changes, has also been suggested as the strongest independent predictor for fetal overgrowth [19,26]. …”
Section: Discussionmentioning
confidence: 99%
“…When fetal body weight increases, more retinol is needed and thus an increased level of RBP4 was observed. Third, it has been suggested that fetal growth is influenced by certain metabolic factors other than glucose [26]. In addition, maternal hypertriglyceridemia is regarded as a significant predictor for fetal overgrowth [11].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that the fetal nutritional environment was the key determinant of later-life obesity [2][3][4][5], which can be explained by "metabolism programming" [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%